Relationship Patterns of Extremist Convicted Husbands and Wives in Indonesia - Bidayati, Kholis; al-Maliki, Muhammad Alwi; Ramadhan, Suci (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This paper examines the relationship patterns of extremist married couples in Indonesia. The analysis was carried out using the descriptive analysis method on the data collected through literature searches by utilising previous research reports from certain agencies and mass media reports related to convicted extremist couples in Indonesia. The results showed that there were two patterns of relationships formed between husband-and-wife terrorist couples. In the early phase of pre-ISIS (Islamic State of Iraq and Syria) women, the wife played more of a role as a follower of her husband (own property), while in the next phase (ISIS Cluster), there was a shift in the relationship between husband and wife terrorist couples, where the relationship that occurs is senior-junior partner; the wife is not just a follower but rather actively and independently in making decisions to become part of extremists to terrorists, both as seniors and juniors from their husbands. This shows the changing role of women in acts of terror, in line with changes in the husband-wife relationship of extremist couples. These phenomena can influence each other. The independence that women have begun to show in their involvement in the extremist world requires the state, apparatus, and society to see women from a different perspective. Women are not always the victims of extremist acts in the family.